Clitic phenomena in European languages - Beukema, F. H. (Frits H.); Dikken, Marcel den, 1965- (Linguistik aktuell ;, 2000)
This book is concerned with a number of central issues in the theory of clitics, a topic that has become much debated in recent years. Mainly written within a recent generative framework, its contrastive approach discusses these issues against the backgro.